Proceedings of the Twelfth ACM International Conference on Web Search and Data Mining 2019
DOI: 10.1145/3289600.3290974
|View full text |Cite
|
Sign up to set email alerts
|

Shaping Feedback Data in Recommender Systems with Interventions Based on Information Foraging Theory

Abstract: Recommender systems rely heavily on the predictive accuracy of the learning algorithm. Most work on improving accuracy has focused on the learning algorithm itself. We argue that this algorithmic focus is myopic. In particular, since learning algorithms generally improve with more and better data, we propose shaping the feedback generation process as an alternate and complementary route to improving accuracy. To this effect, we explore how changes to the user interface can impact the quality and quantity of fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 43 publications
(21 reference statements)
0
8
0
Order By: Relevance
“…In advertising (Charles et al, 2013;Kallus and Udell, 2016;Schnabel et al, 2016;Farias and Li, 2019;Bastani, 2020), using the recorded clientele information, the retailer can send more targeted product promotions-either in mail or online-to different existing and potential customers. In news recommendation (Li et al, 2010(Li et al, , 2011Zeng et al, 2016;Karimi et al, 2018;Schnabel et al, 2019;Lee et al, 2020;Schnabel et al, 2020), the content provider may stream different news articles and/or media content to users with different digital footprints and perceived interests. In online education (Mandel et al, 2014;Lan and Baraniuk, 2016;Hoiles and Schaar, 2016;Bassen et al, 2020), an institution may want to offer different education plans to different students based on their varied learning styles (visual learner v.s.…”
Section: Introductionmentioning
confidence: 99%
“…In advertising (Charles et al, 2013;Kallus and Udell, 2016;Schnabel et al, 2016;Farias and Li, 2019;Bastani, 2020), using the recorded clientele information, the retailer can send more targeted product promotions-either in mail or online-to different existing and potential customers. In news recommendation (Li et al, 2010(Li et al, , 2011Zeng et al, 2016;Karimi et al, 2018;Schnabel et al, 2019;Lee et al, 2020;Schnabel et al, 2020), the content provider may stream different news articles and/or media content to users with different digital footprints and perceived interests. In online education (Mandel et al, 2014;Lan and Baraniuk, 2016;Hoiles and Schaar, 2016;Bassen et al, 2020), an institution may want to offer different education plans to different students based on their varied learning styles (visual learner v.s.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, analogical search engines should help to reduce the cognitive effort required in the process, for example by proactively retrieving results that are 'usefully' misaligned such that searchers can better recognize (as opposed to having to recall) salient constraints and refine their problem representation. This process is deeply exploratory [93,115,118] in nature, and suggest the importance of both providing end-users a sense of progress over time [103] as well as adequate feedback mechanisms for the machine to adjust according to the changing end-user search intent [72,95,96]. For example, while the machine may 'correctly' recognize a significant anaogical relevance at a higher level of purpose representation and recommend macro-scale mechanisms to a scientist who studies nano-scale phenomena (P1 Study 1 ) or solid and semiconductor-based cooling mechanisms to a scientist in liquid and evaporative cooling systems (P3 Study 1 ), these analogs may be critically misaligned on the specific constraints of the problem (i.e.…”
Section: Support Purpose Representation At Different Levels Of Abstra...mentioning
confidence: 99%
“…They evaluated their classification model by performing qualitative data analysis and found that the six characteristics in the model are consistent with those interaction features which built a preliminary practice to study user interaction/behavior via Information Foraging Theory. Recent work [18] studies the influence of feedback data in a movie recommendation system by altering the user interface using information scent and information access cost and found that the primary task of selecting a movie to watch improves the implicit feedback data.…”
Section: Information Foraging Theorymentioning
confidence: 99%